Influence of Parent’s Socio-Cultural Capital on the Personality Development of Secondary Schools Students in South Punjab - Muhammad Nausher; Dr. Nouman Khaliq (Corresponding Author); Prof. Dr. Muhammad Iqbal Zafar (Journal of Religion and Society, 2025)
The current research paper analyses the impact of the socio-cultural capital of the parents on the personality of the secondary school students of South Punjab in Pakistan. The study is based on the theory of capital proposed by Pierre Bourdieu who studies the influence of parental education, family income, language use, study behavior, and social assets on cognitive, affective, social, behavioral, moral, and physical development of students. The quantitative design entailed a stratified random sample of 600 students who were selected in 30 urban and rural, divided into 30 public secondary schools. A structured questionnaire was used to collect data which has proven to be highly reliable (Cronbachs 0.70 and above). The analysis (statistical tests that were performed that included descriptive statistics and correlation tests) demonstrated a strong positive correlation between the socio cultural capital of parents and the personality growth of students. The research presents the significance of a comprehensive family involvement and interventions to curb the effects of socio-cultural discrepancies, achieve fair education results, and boost the general development of students. Policy suggestions highlight the need to educate parents through programmes, community-based interventions, and provision of resources in order to assist the disadvantaged families. These results add up to the available literature on the multidimensional influence of socio-cultural capital in a South-Asian context. Keywords: Socio-cultural capital, personality development, secondary education, the region of South Punjab, Bourdieu theory.